Geospatial Multi-Criteria Suitability Analysis Of Proposed Lagos State Airport Site Selection - Isa Adekunle Hamid-Mosaku; Paul Ugochukwu Ngadi; David Oluwafemi Osoba; Idris Ademola Abdulkareem; Peter Akpabio; Kehinde Morenike Oseni; Adewale Anthony Ademuyiwa; Solomon Adetayo Adegoke (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
The Federal Government of Nigeria recently announced the plan for new airports across the country in order to ease the air transportation system across the country and its connectedness to other parts of the world. However, the adequacies of the declared sites were not empirically supported through a carefully designed suitability assessment; that assured their appropriateness environmentally and geospatially. Thus, this paper examines the geospatial suitability evaluation of the proposed Airport in the Eti-Osa Local Government Area in Lagos State. A multi-criteria suitability analysis (MCSA) concept in a geospatial environment was adopted, using the analytic network process (ANP)del based on reviewed criteria for the airports' site suitability selection. Different thematic layers of the land cover for the assessment were achieved through the geospatial capabilities of Geographic Information System and Remote Sensing, with the various factors’ priorities from the ANP model in the final analysis of alternative suitability sites for this proposed airport. The final suitability model revealed different levels of this suitability for consideration by relevant decision-makers for better-informed decisions about the project.